Antimicrobial activities of untreated and grape vinegar treated selected vegetables against common food borne pathogens - Jyotsana Singh; Amar P Garg (Journal of Biology and Medicine - Peertechz Publications, 2023)
In the post-Covid-19 era, plant-based diets and products have become more popular. Fruit vinegar is considered a healthy drink, rich in bioactive compounds like organic acids, polyphenols, flavonoids and alkaloids that provide several beneficial properties. Fruit vinegar also contains several beneficial nutrients like amino acids, sugars, vitamins and minerals. They provide energy, regulate cell metabolism, immunity, antioxidation, anticoagulation and help in the improvement of brain development. Vinegar is also known for its strong antimicrobial properties against foodborne pathogens. The aim of the present investigation was to find out the antimicrobial activities of grape vinegar against common food-borne pathogens and to see whether common vegetable lose their antimicrobial activities when soaked with grape vinegar or gain. The vegetables used in the present investigation were randomly collected from the local market. We have evaluated the antimicrobial properties of untreated and grape vinegar (GV) treated selected vegetables against Escherichia coli (ATCC8739), Bacillus subtilis, Staphylococcus aureus (ATCC 6539), Shigella flexneri (ATCC 12022), Salmonella typhi (ATCC 14028), Cronobacter sakazakii (ATCC 29544), Vibrio parahaemolyticus (ATCC 17802), Vibrio cholera (ATCC 3906) and Pseudomonas aeruginosa. Based on the randomized survey, commonly used vegetable ginger (Zingiber officinale), garlic (Allium sativum), onion (Allium cepa), raw papaya (Carica papaya), white radish (Raphanus sativus) and green chilli (Capsicum annuum) were selected for the assessment of their antimicrobial activities. Different phytochemicals were found in water extract and grape vinegar-treated vegetables. Our results suggested that in general, grape vinegar-treated vegetables showed higher antimicrobial activities against all tested food-borne pathogens, but onion, garlic, green chillies and white radish revealed drastically higher activities. Hence, it is suggested that onion, garlic, green chillies and white radish should preferably be used after soaking with grape vinegar. All vegetables except garlic and white radish showed very little antimicrobial activity against B. subtilis. V. cholera was highly sensitive to grape vinegar-treated vegetables except for garlic. Similarly, V. parahaemolyticus was highly sensitive to grape vinegar-treated green chillies, white radish, raw papaya, and onion. Shigella flexneri also showed greater sensitivity to GV-treated green chillies and white radishes. Pseudomonas aeruginosa was sensitive to ginger and green chillies only. It may safely be concluded that grape vinegar-treated vegetables are beneficial to fight against food-borne infections. The vegetable when soaked with grape vinegar did not lose their antimicrobial activities rather they gained the antimicrobial components from grape vinegar. Our studies revealed that white radish, ginger, green chilies, and onion should be used after soaking in grape vinegar while garlic and raw papaya should be eaten without treatment with grape vinegar.